An in situ elemental migration on a nanosize Cu–Sn interface in a microscope - Ang Li; Yu Tao; Hui Lu; Shihang Qiao; Shanshan Liu; Yilin Jiao; Lilin Xie; Yanhui Chen (Journal of Materials Research and Technology, 2023)
Elemental migration between different elements is intrinsic process for diffusion. Most of the study focused on the presentative shape or size on of Kirkendall pores, yet on the intermediate migration process. A dynamic elemental transition trajectory recording provides realtime diffusion process on a Cu–Sn nanoscale interface is thus necessary to disclose intermediated reaction on diffusion process. In this work, elemental dynamic diffusion processes were recorded and analysed on a microsize Cu–Sn couple lamella by in situ transmission electron microscopy up to Sn melting point. Factors of atomic quantity, contact condition and temperatures were studied on its diffusion behaviours. The work shed new light on conventional metallographically interfaces diffusion and provide intrinsic clues for solder design.